2001
DOI: 10.1104/pp.126.4.1459
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Biological Characterization of Intracellular Carbonic Anhydrase from the Marine DiatomPhaeodactylum tricornutum  

Abstract: A single intracellular carbonic anhydrase (CA) was detected in air-grown and, at reduced levels, in high CO 2 -grown cells of the marine diatom Phaeodactylum tricornutum (UTEX 642). No external CA activity was detected irrespective of growth CO 2 conditions. Ethoxyzolamide (0.4 mm), a CA-specific inhibitor, severely inhibited high-affinity photosynthesis at low concentrations of dissolved inorganic carbon, whereas 2 mm acetazolamide had little effect on the affinity for dissolved inorganic carbon, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
90
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 62 publications
8
90
0
Order By: Relevance
“…1B, subsection a) or the coding region of mptca1 (accession no. AF414191; Satoh et al, 2001) with a deleted termination codon inserted between pre138 and egfp (Fig. 1B, b).…”
Section: Vector Constructsmentioning
confidence: 99%
See 3 more Smart Citations
“…1B, subsection a) or the coding region of mptca1 (accession no. AF414191; Satoh et al, 2001) with a deleted termination codon inserted between pre138 and egfp (Fig. 1B, b).…”
Section: Vector Constructsmentioning
confidence: 99%
“…The gene for the presequence of PtCA1 precursor, pre138 ( Fig. 1A; Satoh et al, 2001; accession no. AF414191), was ligated directly with egfp (Fig.…”
Section: Vector Constructsmentioning
confidence: 99%
See 2 more Smart Citations
“…A b-carbonic anhydrase in the marine diatom P. tricornutum (PtCA1), thought to be one of the crucial chloroplastic components of the CCM (Satoh et al, 2001;Tanaka et al, 2005), is known to be regulated strictly by the ambient [CO 2 ] and light . A promoter region of the PtCA1 gene (ptca1) was isolated previously, and it was demonstrated that the critical CO 2 -response sequence was located downstream 270 bp relative to the transcription start site .…”
mentioning
confidence: 99%